ANALYSIS AND DESIGN OF DISTRIBUTED SYSTEM FOR MONITORING COMPUTER INFRASTRUCTURE MANAGEMENT BASED ON CLIENT/SERVER BY USING WINDOWS MANAGEMENT INSTRUMENTATION TECHNOLOGY - Mr. Musawarman (Journal of Information Technology and Its Utilization, 2019)
This research aims to analyze and develop a system for monitoring computer infrastructure management in real time (real-time monitoring). The developed system was a distributed system that would help IT Administrators work at the Center for Computing and Information Technology Faculty of Engineering Universitas Indonesia (CCIT FTUI) to monitor the computer infrastructure in real-time. The Real - time referred to system that was able to do direct monitoring to computer infrastructure, and quickly able to transmit data status of the device. Limitations of the current monitoring process was that the IT Administrator checks directly into the computer lab room if there were problems related to a computer or cable that was not connected from the computer system based on a report from teachers or students.         The developed monitoring system was a client/server based system that used network infrastructure so that the computer infrastructure could be optimally monitored. The modules used in this research are computer input and output modules, and installed applications or system services. This research is expected to be able to overcome the problems associated with computer infrastructure’s performance, conduct supervision and centralized control in helping the problems that often occur during learning process or examination. Keywords: Monitoring, Computer Infrastructure Management, Distributed System, Computer Network, Real-time.